Alternative test by the bill of 2013 for health reform in Colombia (2013)
Within the regulatory framework governing the Social Security System in Colombia, is Act 100 of 1993 whose objectives were based on the provision of quality health services and is a fundamental principle that the right to life. To give effect to its objectives, the creation of EPS, IPS and FOSYGA as actors within the system where your job is to manage public funds by ensuring that all Colombians enjoy an excellent health and thus must conduct was established advocacy and prevention. Years later, he finally recognizes that there are flaws in the previous system and reform the same where EPS and FOSYGA are removed to make way for another administration with a more global approach to social responsibility that has for raises the System users Keywords: POS, POS NO, SISBEN, subsidized scheme, Contributory Scheme